Determining factors in the performance of integrated vocational education schools (REGE Revista de Gestão, 2022)
Purpose – The purpose of this paper is to identify the determining factors in the performance of integrated vocational education schools, in addition to management characteristics and specificities.Design/methodology/approach – By means of a descriptive study with a qualitative approach, a case study was conducted in two schools located in the cities of Cotia and São Roque.Findings – The following factors were identified: engagement and commitment of teachers; motivation and focus of teachers and students; team of professionals; commitment and focus of students; family involvement; leadership and climate and selection of students. The following characteristics were observed: participative leadership associated with the use of management tools; pedagogical leadership in partnership with the school community; monitoring of student performance; performance assessment and training of teachers related to career plan; selection of students and actions along the community.Research limitations – The results reflect the vision of the schools’ managers and teachers and not that of the managing institution. There is no intention whatsoever to obtain generalization to other ETECs but rather inferences that could shed light on future studies.Practical implications – This research ratifies what has already been proven in the literature, showing that there are no isolated factors that interfere with performance, but an interrelationship among them, given the characteristics and peculiarities of each school.Originality/value – This study is expected to contribute to guiding school managers and teachers in the search for quality education, whether vocational or regular basic education.